2013
DOI: 10.1002/art.37920
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain in Ankylosing Spondylitis: A Psychophysics and Brain Imaging Study

Abstract: Objective. To determine whether there is a neuropathic component in ankylosing spondylitis (AS) back pain and to delineate gray matter brain abnormalities associated with AS.Methods. Seventeen patients with back pain secondary to AS who were not receiving biologic agents and 17 age-and sex-matched healthy controls consented to participate in the study and were assessed using the painDETECT instrument (scores of <12 indicating low probability of neuropathic pain) and the McGill Pain Questionnaire. Mechanical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 55 publications
4
83
0
5
Order By: Relevance
“…Dysregulation of central pain processing mechanisms and central sensitization is the underlying pathology of NP. Wu et al (12) showed that higher painDETECT scores in AS patients were found to be correlated with thinning of the primary somatosensory cortex and thickening of the primary motor cortex. The study of Wu et al is valuable since it showed objective findings of central sensitization, which supports the reliability of painDETECT in assessing neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of central pain processing mechanisms and central sensitization is the underlying pathology of NP. Wu et al (12) showed that higher painDETECT scores in AS patients were found to be correlated with thinning of the primary somatosensory cortex and thickening of the primary motor cortex. The study of Wu et al is valuable since it showed objective findings of central sensitization, which supports the reliability of painDETECT in assessing neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one recent study that indicated the presence of NP in AS (12). In that study, correlations of painDETECT scores and abnormal brain gray matter findings were shown.…”
Section: Introductionmentioning
confidence: 92%
“…Patients with AS usually have sensory loss, such as loss of proprioception (44) or decreased mechanothermal sensitivity in the affected dermatome (23). Both pain and sensory loss can cause fatigue and deficits in attention (45,46), which might involve common central mechanisms, either directly affecting brain areas associated with executive functioning (23,47,48), or indirectly regulating the attention functioning by highlevel sensory-attention integration via the secondary somatosensory cortex (43,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Both pain and sensory loss can cause fatigue and deficits in attention (45,46), which might involve common central mechanisms, either directly affecting brain areas associated with executive functioning (23,47,48), or indirectly regulating the attention functioning by highlevel sensory-attention integration via the secondary somatosensory cortex (43,(49)(50)(51). Our findings (of abnormalities in cortical thickness of frontoparietal executive control networks and of the coupling of cortical thinning in the secondary somatosensory cortex and the contralateral parietal orienting network) support the notion of both the direct and indirect mechanisms mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation